The Effect of Symmetrical Involvement of the Knee Joints in Moderate Osteoarthritis on Individuals' Report of Pain and Function (Part Two of a Preliminary Study): Knee Injury and Osteoarthritis Outcome Score - Zeinab Niki; Behrooz Melyanian; Zahra Sadat Rezaeian (Vesnu Publications, 2016)
Introduction: Knee osteoarthritis is a common age-related disorder. The aim of the present study was to determine the effect of symmetrical involvement of the knee joints on subjects' report of symptoms, pain intensity, daily activities, and quality of life (QOL) using the Knee Injury and Osteoarthritis Outcome Score (KOOS) in subjects suffering from moderate knee osteoarthritis. Materials and Methods: The 20 subjects suffering from moderate knee osteoarthritis were purposefully divided into two groups of symmetric and asymmetric knee joints involvement. After obtaining informed consent forms, demographic information was obtained and each subject completed the Persian version of KOOS. The scores were compared using Mann-Whitney U test both for each individual item and for each section. Results: The pain intensity in going up stairs (P = 0.030), sitting or lying (P = 0.040), difficulty in getting in and out of the car (P = 0.010), rising from bed (P = 0.009), turning over in bed (P = 0.020), rising from a sitting position, putting on socks/stockings, and bathing (P = 0.050) was higher in the symmetric group. In addition, the symmetric group had more complaints of lack of confidence in their knee (P = 0.030). Thus, daily function and QOL scores were significantly lower in the symmetric group (P = 0.040, P = 0.020, respectively). Conclusion: It seems that the ability to perform daily functions and QOL were significantly lower in the symmetric group than the asymmetric group. Further investigations are recommended in this respect for a better understanding of the functional limitations of these individuals in daily life.